Attitude and perception of gender equity among students and teachers of a rural school in West Bengal: A mixed-method approach - Jha, Sweety Suman (J Educ Health Promot, 2020)
INTRODUCTION: “Gender” denotes the differences in the social roles of different sexes. This interaction results in variable health outcomes and care-seeking behavior. The present study was conducted to find out the attitude of school-going adolescents regarding gender equity and also to explore teachers’ perceptions in this context in a school of tribal belt of West Bengal. MATERIALS AND METHODS: A cross-sectional, mixed-method study was conducted among the students of classes eight to twelve, chosen by complete enumeration technique, with a predesigned, pretested validated questionnaire. The questionnaire was based on Gender Equitable Men scale and International Men and Gender Equality Survey questionnaire, comprising the following domains: ‘Gender restrictions’, ‘Gender attributes’, and ‘Gender domination’. The respondents were categorized into ‘high’, ‘moderate’, and ‘low’ groups as per their domain-wise attitude scores. In-depth interviews (IDIs) were conducted among seven teachers chosen purposively. Thematic analysis was done with the qualitative data. RESULTS: Out of 191 students, 112 were girls (58.6%) and 47 belonged to scheduled tribe category (24.6%). Overall, 170 (89.0%), 80 (41.9%), and 96 (50.3%) students had a high gender-equitable attitude regarding the domains of ‘gender restrictions’, ‘gender attributes’, and ‘gender domination’ respectively. Girls had higher percentage of high gender-equitable attitude in all the three domains (92.0%, 57.1%, and 50.9%, respectively). Regarding ‘gender restrictions’, 91.2% had high gender-equitable attitude in lower age group, compared to 81.4% in higher age group. Among the lower and higher age groups, 52.7% and 41.9% respectively, had high gender-equitable attitude on ‘gender domination’. Gender inequality amidst poverty, women deprived of health care, and gender violence were the major themes derived from the IDIs. CONCLUSION: Girls had a better attitude toward gender equity. Laws regarding gender dominance and violence should be focused. Conducting intensified awareness campaigns on gender equity and addressing women's right to health is a much-needed timely intervention for the health of womenfolk.